RESULT OF BONE BLOCKING SURGERY IN COMBAT ATHLETES WITH ANTERIOR SHOULDER INSTABILITY: A PROSPECTIVE STUDY - BALDAN,ARTHUR RODRIGUES (2022)
ABSTRACT Objective: This study aims to understand the way fighting athletes respond to bone block surgery in the treatment for shoulder instability. Methods: Prospective clinical study with competitive fighters with shoulder instability who underwent bone block surgery from 2013 to 2016, followed by a postoperative rehabilitation protocol. For the evaluation, eight combat athletes with anterior shoulder instability were treated, with a total of nine shoulders, since one athlete underwent bilateral surgery. All patients signed the Free and Informed Consent Form. The evaluation protocol included medical consultation, radiography of the operated shoulder, degree of active and passive lateral rotation; degree of active and passive elevation; visual analogue scale (VAS) for pain; Athletic Shoulder Outcome Rating Scale (EROE; acronym in Portuguese) scores; Western Ontario Shoulder Instability Index (WOSI), and American Shoulder and Elbow Surgeons (ASES). Results: We observed a decrease in the range of passive and active movement in the recent postoperative period. In later postoperative, values were close to those in the preoperative period at the end of the follow-up. There was improvement in pain, and in all ASES, WOSI and EROE scores no complications were documented. As for returning to sport, two athletes did not return, one of them due to shoulder pain and the other due to retirement. Conclusion: Bone block surgery has shown good functional results in uncomplicated combat athletes. Level of Evidence IV, Prospective Case Series.